Association Between Weight-Adjusted Waist Index and Cognitive Function in Older Adults Without Diabetes: A Cross-Sectional Study - Wang Q; Yin Y; Liu W; Li L; Wang Z; Tian Y; Fan J (Clinical Interventions in Aging)
Qing Wang,1,* Yishan Yin,2,* Wei Liu,3,* Lingyu Li,1 Zhen Wang,1 Yue Tian,1 Jing Fan1 1Department of Laboratory Medicine, Qilu Hospital of Shandong University Dezhou Hospital, Dezhou, Shandong, 253000, People’s Republic of China; 2Department of Orthopedics, The Armed Police Forces Hospital of Shandong, Jinan, Shandong, 250000, People’s Republic of China; 3Department of Emergency Critical Care Medicine, Qilu Hospital of Shandong University Dezhou Hospital, Dezhou, Shandong, 253000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Fan, Department of Laboratory Medicine, Qilu Hospital of Shandong University Dezhou Hospital, Dezhou, Shandong, 253000, People’s Republic of China, Email sddzfanjing@163.comBackground: This study investigates the correlation between the weight-adjusted waist index (WWI) and cognitive performance in the senior American population, focusing on those without diabetes from 2011 to 2014.Methods: We analyzed data from the 2011– 2012 and 2013– 2014 National Health and Nutrition Examination Surveys (NHANES), focusing on non-diabetic participants aged 60 and older who completed cognitive tests: Establish a Registry for Alzheimer’s disease (CERAD), the Animal Fluency test (AFT), and Digit Symbol Substitution test (DSST). WWI was calculated using waist circumference divided by the square root of body weight. We employed linear univariate and multivariate analyses, along with curve fitting, we conducted subgroup and interaction analyses to elucidate the relationships under investigation.Results: The study incorporated a cohort of 1649 participants aged 60 years and older, each with a complete set of data, enabling a thorough analysis. After adjusting for confounding factors, significant negative correlations were found between WWI and both CERAD (β: − 0.48; 95% CI: − 0.92 to − 0.05; P=0.03) and DSST (β: − 1.15; 95% CI: − 2.09 to − 0.21; P=0.017) scores, suggesting a link to cognitive decline. No association was found with AFT scores. The relationship between WWI and DSST was found to be nonlinear (P for non-linearity=0.022). Additionally, the association between WWI and CERAD was also observed (P for non-linearity=0.042). However, linear relationships were observed between WWI and AFT (P for non-linearity=0.418). The subgroup analysis was overall stable.Conclusion: Our cross-sectional study indicates a strong link between a high WWI and reduced cognitive function in non-diabetic older Americans, as shown by CERAD and DSST scores. Attaining an optimal WWI may be vital for cognitive decline, highlighting its role in a potential preventative approach.Clinical Trial Registry Number and Website Where It Was Obtained: The study design and data are publicly accessible at www.cdc.gov/nchs/nhanes/.Keywords: cognitive function, non-diabetic, NHANES, cross-sectional study, weight-adjusted-waist index, WWI